Multi-stage reaction and separation systems of a CO2-based hydrometallurgical process - Zhao, Huangjing; Zhou, Xiaozhou (2022)
The present invention is a CO2 based hydrometallurgical multistage reaction and separation system comprising: a pre-washing device configured to fully mix the feedstock, such as industrial solid waste, mineral and mine tailings with auxiliary reagents and water at specific ratio, a reactor configured to treat the washed slurry with CO2 bubbling and discharge the treated slurry to the next stage, multistage separators configured to separate solid particles from treated slurry and recycle the unreacted solids back into the pre-washing device, a by-product preparation device configured to generate calcium and magnesium based products from filtrate containing target elements, a water recirculating device configured to recycle the remaining liquor back to the system. The present invention ensures the whole system is able to continuously and consistently react at maximum capacity through continuous slurry feeding and CO2 bubbling into the reactors which also enables multistage circulating reaction.